2021
DOI: 10.1371/journal.pgen.1009433
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional rewiring of the GcrA/CcrM bacterial epigenetic regulatory system in closely related bacteria

Abstract: Transcriptional rewiring is the regulation of different targets genes by orthologous regulators in different organisms. While this phenomenon has been observed, it has not been extensively studied, particularly in core regulatory systems. Several global cell cycle regulators are conserved in the Alphaproteobacteria, providing an excellent model to study this phenomenon. First characterized in Caulobacter crescentus, GcrA and CcrM compose a DNA methylation-based regulatory system that helps coordinate the compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…Between 31 and 53 GANTC sites were repeatedly not detected as methylated on one or both strands in each of the four wild-type strains (see Data set S2 at doi.org/10.6084/m9.figshare.16556205 ), as has also been observed in other species ( 17 , 46 ). However, further work is required to determine if this hypomethylation is biologically meaningful (e.g., CcrM cannot access the site due to binding of another protein [ 46 ]) or if it reflects technical artifacts (e.g., low sequencing coverage).…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…Between 31 and 53 GANTC sites were repeatedly not detected as methylated on one or both strands in each of the four wild-type strains (see Data set S2 at doi.org/10.6084/m9.figshare.16556205 ), as has also been observed in other species ( 17 , 46 ). However, further work is required to determine if this hypomethylation is biologically meaningful (e.g., CcrM cannot access the site due to binding of another protein [ 46 ]) or if it reflects technical artifacts (e.g., low sequencing coverage).…”
Section: Resultssupporting
confidence: 61%
“…Supporting this conclusion, no motif was enriched in the promoter regions of symbiosis, carbon source, or cell cycle-regulated genes, and we did not detect any motifs that were methylated specifically in bacteroids. However, we cannot rule out that one or more methylated motifs may influence specific gene expression during free-living growth, differentiation, or N 2 -fixation through extended motifs or proximity to other promoter elements, similar to the interplay between CcrM and GcrA during cell cycle regulation in C. crescentus ( 20 , 46 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, it has been found that the most significant tetramers for ML algorithms largely correspond to the motif that was found in the reference paper for the data used [2] with the MEME program, as presented in Figure 2.…”
Section: Discussionsupporting
confidence: 66%
“…Our work has been previously published as a Master's Thesis at the Universitat Oberta de Catalunya (UOC) [1]. The DNA sequences used as positive data were extracted from the article by Adhikari et al [2], obtained using the ChIP-seq technique with the GcrA TF in the bacterial organism Brevundimonas subvibrioides.…”
Section: Introductionmentioning
confidence: 99%